Inputs to optimize risk communication: testing preferences in icons for emergencies - Ramirez, Rodrigo (InfoDesign, 2023)
Disaster Risk Management (DRM) introduces a paradigm change from mitigating impacts to preparedness. Communication becomes fundamental for a safe experience. Designing information has a decisive role in optimizing the experience. Following their principles, messages can be optimized for emergencies. Everyday information tools appear to be less effective during and after an emergency. Icons constitute a paradigm of visual communication, however, usually these are not evidenced in their performance. This paper presents the testing process of an open-access icon set for emergencies, specifically the preferences test. 283 responses evidence how participants associate representations with given concepts. Communication based on icons contributes to establishing preferences, constituting a support for the communication of risk. Integrating communication to DRM contributes to an effective articulation of risks. Results are discussed as three insights: (1) Familiarity, (2) Performance, (3) Knowledge for reducing risks. Information design contributes to facilitating such a process.